Aortic regurgitation: epidemiologic, etiologic, and pathophysiologic characteristics - G. A. Ignatenko; N. T. Vatutin; G. G. Taradin; A. N. Shevelok; I. V. Rakitskaya (Klinicist)
The presented review concerns aortic regurgitation which occupies a significant place in the structure of valvular heart disease. The detailed anatomic and physiologic description of the aortic valve is provided. The characteristics of sinotubular, ventricular-aortic junctions, and virtual aortic annulus are presented. There are data about prevalence of aortic regurgitation on the basis of results of population studies, indicating the increase in incidence of aortic regurgitation among individuals older 70–74 years. The detailed etiologic structure of this valvular pathology is described with specifying of the most common causes of both aortic disease and aortic cusps alterations. In particular, there are some aortic diseases, resulting in acute aortic regurgitation, including acute aortic dissection and paravalvular regurgitation in incompetence of the prosthetic aortic valve; in chronic one – idiopathic dilation of the aortic root, inherited connective tissue dysplasias (Ehlers–Danlos, Marfan, and Loeys–Dietz syndromes), bicuspid aortic valve, aortitis of various origin, seronegative arthropathies (reactive, psoriatic arthritis, ankylosing spondylitis) etc. Infective endocarditis and traumatic exposure are commonly responsible for development of acute regurgitation due to aortic cusps abnormalities. Chronic aortic regurgitation as a consequence valve defects occurs in rheumatic heart disease, degenerative changes, congenital anomalies, systemic connective tissue diseases (systemic lupus erythematosus, rheumatoid arthritis), non-specific aortoarteritis, etc. The special attention is paid to pathophysiologic features of acute and chronic aortic regurgitation in the review. Acute aortic regurgitation is characterized by sudden increase in end-diastolic volume and due to the noncompliant left ventricle of normal size, it undergoes abrupt exposure a significant pre-load and after-load which results in decrease of left ventricle systolic function and stroke volume despite on relative preservation of contractile function of myocardium. In contrast to acute aortic regurgitation it is remarkable in its chronic form slow, progressive influence by increased overload of the left ventricle with possibility to adapt driven by its gradual dilation and hypertrophy.